Pengaruh Disiplin Kerja dan Motivasi Terhadap Kinerja Pegawai di SMK Negeri 5 Bandung - Azfi Shafia Marwah Anandhita; Alda Ramadhika (Fakultas Ekonomi Universitas 45 Surabaya, 2025)
This study aims to analyse the influence of work discipline and motivation on employee performance at 5 Vocational High School Bandung. Work discipline and motivation are important factors in improving employee performance, especially in an educational environment. This research employs a quantitative method. The population in this study is teaching staff at 5 Vocational High School Bandung. The sample used is 98 people. The sampling technique used is nonprobability sampling with a census or total sampling type. The data source used in this study is primary data with research instrument used in form of a questionnaire via g-form which is distributed directly to respondents. The scale is the Likert scale. Analysis of data used is multiple linear analysis using SPSS software version 26. The results of the study indicate that work discipline has a positive effect on employee performance at 5 Vocational High School Bandung, and motivation also has a positive effect on employee performance. Simultaneously, work discipline and motivation positively influence employee performance at 5 Vocational High School Bandung. Work discipline and motivation contribute 57.4% to employee performance at 5 Vocational High School Bandung, while the remaining 42.6% is influenced by other factors not examined in this study.